Groups, Algorithms and Programming (GAP) and the Nonabelian Tensor Square of Groups of Order 8q - Rashid, S; ., . (International Journal of Engineering and Technology, 2018)
In this paper, the software package Groups, Algorithms and Programming (GAP)Â Â is used to verify the hand calculation ofÂ the nonabelian tensor square for groups of order 8q, where q is an odd prime.Â